Tributgesetzgebung und ihre Umsetzung in den Vizekönigreichen Peru und Neuspanien im Vergleich - Albiez-Wieck, Sarah (Anuario de Historia de América Latina, 2017)
Indigenous and afrodescendant tribute payments constituted the central manifestation of the colonial relationship between the Americas and the Spanish crown. This article outlines the development of colonial tributary legislation and its implementation in the viceroyalties of New Spain and Peru from the 16th to the 19th century. It focuses on tribute categories as decisive factors for the formation of the colonial society. The comparative approach reveals that the major differences between New Spain and Peru lay first in the tribute categories for “migrants” and second in the varying degree of implementation of tribute obligations among the afrodescendant population.